The Impact of globalization on the culture of silence, and the I-Taukei youth in Fiji - Naivalucava, Vilikesa Ratubulewa (KDI School, 2012)
This study intends to verify the notion that the current youth of Fiji tend to be more vibrant and determined in pursuit of their rights. Slowly but surely they are moving away from the culture of silence under the influence and impact of globalization. Education provides them with the means and audacity to question the status quo, challenging chiefs and government, raising questions in relation to decisions and policies. The affinity to be vociferous however is viewed with suspicion and construed as lack of respect, unbecoming of Fijian ethos. Under the British Colonial regime, and ever since independence, Fiji has undergone significant cultural transformation affected greatly by the processes of globalization. Even so the “culture of silence” an important and unique Fijian cultural heritage remains ingrained among all generations of Fijians. The question then is whether the impact of globalization in transforming culture could be minimized or should it be maximized as a vehicle for change to engender positive participation on policy development at the national level? Whilst there is no denial that the processes of globalization are inevitable, the choice therefore may be one between resistance or modification to capitalize on globalization.
Thesis(Master) --KDI School:Master of Public Polic,2012